2012
DOI: 10.1007/s00234-012-1084-y
|View full text |Cite
|
Sign up to set email alerts
|

Is general anaesthesia preferable to conscious sedation in the treatment of acute ischaemic stroke with intra-arterial mechanical thrombectomy? A review of the literature

Abstract: Intra-arterial mechanical thrombectomy under general anaesthesia is associated with poor outcomes in observational studies. It is reasonable to offer conscious sedation as the preferred option where adverse patient factors such as agitation are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
1
31
0
4
Order By: Relevance
“…Retrospective analyses of the hemodynamic parameters of patients underwent mechanical recanalization for AIS found that GA was associated with a lower minimum systolic, diastolic, and mean blood pressure than MAC, and that higher systolic blood pressure was associated with better outcomes (21). Other studies, however, have not found significant trends in hemodynamic variation between GA and MAC (16).…”
Section: The Potential Benefits Of Monitored Anesthesia Care: Why?mentioning
confidence: 76%
See 3 more Smart Citations
“…Retrospective analyses of the hemodynamic parameters of patients underwent mechanical recanalization for AIS found that GA was associated with a lower minimum systolic, diastolic, and mean blood pressure than MAC, and that higher systolic blood pressure was associated with better outcomes (21). Other studies, however, have not found significant trends in hemodynamic variation between GA and MAC (16).…”
Section: The Potential Benefits Of Monitored Anesthesia Care: Why?mentioning
confidence: 76%
“…For example, one multicenter study showed that GA was associated with worse functional outcomes as assessed by the mRS than monitored anesthesia care (MAC), based on data from 980 patients who underwent mechanical recanalization (13). Other retrospective studies have come to similar conclusions, with GA associated with worse functional outcomes (i.e., a mRS score >2) (14,15), parenchymal hemorrhage (16), and higher in-hospital mortality (16). A recent metaanalysis of nine studies with 1956 patients found that GA had a lower odds ratio (OR) for good functional outcome (OR= 0.43; P<0.01) and successful recanalization (OR=0.49; P< 0.01), and a higher OR for mortality (OR=2.59; P<0.01) and respiratory complications (OR= 2.09; P<0.01) (17).…”
Section: General Anesthesia Versus Monitored Anesthesia Care For Mechmentioning
confidence: 98%
See 2 more Smart Citations
“…It is important to remember that endovascular thrombectomy requires general anaesthetic, although some recent studies have shown that it is preferable to carry out the procedure using conscious sedation 31,32 . Despite the potential efficacy of endovascular treatment, in particular using the stent retriever technology that results in higher rates of optimal perfusion, its higher cost compared to other technologies 33 adds to the challenge of the use of this new technology and further studies are needed to prove its cost-effectiveness.…”
Section: Possible Limitationsmentioning
confidence: 99%